Benson Relaxation Intervention to Reduce Anxiety in Chronic Kidney Disease Patients at RSUD Kanjuruhan - Wiwit Dwi Nurbadriyah; Fikriana, Riza; Rika Dian Mariana; Dhita Kurnia Sari; Ardhiles Wahyu Kurniawan (Journal Of Nursing Practice, 2025)
Background: Chronic kidney disease (CKD) is a significant global health issue affecting individuals across all age groups. A prevalent concern among CKD patients is anxiety, which can disrupt daily activities and overall quality of life. Methods: This study employs a qualitative case study approach to explore the nursing care process for patients with CKD experiencing anxiety. The research involved purposeful sampling and was conducted through three structured client meetings. Results: The findings demonstrate that the Benson relaxation technique significantly reduced anxiety levels in CKD patients. Observations indicated notable improvements in the client's emotional states from the beginning to the conclusion of the study. Conclusion: This research underscores the importance of implementing non-pharmacological interventions, such as Benson relaxation, alongside traditional pharmacological treatments. It is recommended that this relaxation technique be incorporated into daily routines for patients when experiencing anxiety.